Histological characterization of ovarian follicles of Arapaima gigas (Cuvier, 1817) of 12, 18 and 24 months of age - Yong Rojas, Carlos Armando (2020)
The histological description of ovarian follicles of the 12, 18 and 24-month-old paiche (Arapaima gigas) from a fish farm in Iquitos in May 2018 was performed using a convenience sampling. Nine, 13 and 4 fish ovaries of 12, 18 and 24 months, respectively were used. A follicular classification was developed based on the follicular characteristics and based on this, the ovarian follicular ratio, follicular diameters, and the percentage of follicular atresia were determined. The following phases are considered: Perinucleolar (PN), Endogenous vitellogenesis I (VE1), Endogenous vitellogenesis II (VE2) and exogenous vitellogenesis (VEX). The highest frequency of PN follicles was presented at the age of 12 months (p<005), with no significant differences in the frequency of VE1 follicles at 18 and 24 months. VE2 and VEX stages were only observed at 24 months of age. No significant difference was found in the percentage of atresia between ages. The results obtained suggest that the females have apparent characteristics compatible with the onset of an advanced maturation of the ovary from 24 months of age.